Anchored multiplex PCR for targeted next‐generation sequencing reveals recurrent and novel USP6 fusions and upregulation of USP6 expression in aneurysmal bone cyst. Issue 4 (2nd December 2016) - Guseva, Natalya V.; Jaber, Omar; Tanas, Munir R.; Stence, Aaron A.; Sompallae, Ramakrishna; Schade, Jenna; Fillman, Allison N.; Miller, Benjamin J.; Bossler, Aaron D.; Ma, Deqin
Abstract : Primary aneurysmal bone cyst (ABC) is a neoplastic process due to recurrent translocations involving the USP6 gene. By fluorescence in situ hybridization, up to 69% of primary ABCs harbored USP6 translocations; no USP6 translocation was found in secondary ABC or giant cell tumor of bone (GCT). GCT can recur locally, metastasize to the lungs in some cases, and rarely undergo malignant transformation. Differentiating primary ABC from its mimics is important for treatment and prognosis. We evaluated USP6 fusion and expression in 13 cases of primary and 1 case of secondary ABC, and 9 cases of GCT using nucleic acid extracted from formalin‐fixed, paraffin‐embedded tissue and a next generation sequencing (NGS)‐based assay. USP6 fusions including 7 novel fusions and USP6 transcripts were identified in all 13 primary ABCs. Nine cases with strong evidence of fusions showed high levels of USP6 transcripts by reverse transcription‐PCR (RT‐PCR). The remaining four had no detectable USP6 expression by a first‐round of RT‐PCR but the presence of USP6 transcripts was identified by a second‐round, nested PCR. The major fusions were confirmed by RT‐PCR followed by Sanger sequencing. No USP6 fusion or transcript was detected in any of the GCTs or the case of secondary ABC by NGS or by two rounds of PCR. All USP6 translocations resulted in fusion of the entire USP6 coding sequence with promoters of the fusion gene leading to upregulation of USP6 transcription, which is likely the underlying mechanism for ABC oncogenesis. © 2016 Wiley Periodicals, Inc.